Teachers’ Sleep, Religious Tasks, and Suicidal Thoughts: A Preliminary Assessment - Asio, John Mark R.; Jimenez, Edward C. (Future Science / FSH-PH Publications, 2021)
Because of the unexpected and debilitating effect of the current pan-demic, the impact of the pandemic on teachers is detrimental. This paper investigated the public-school teachers' sleep, religious tasks, and suicidal thoughts. The study used a descriptive correlational de-sign with the online survey as the primary data gathering tool. 198 public school teachers from a school's division in Central Luzon, Phil-ippines participated in the online survey. The researchers created the online instrument with validation done by experts. After the data gathering, the study used the following statistical tools to calculate the frequency count, percentage, rank, t-test, and Analysis of Variance with the help of SPSS 22. Results show that teachers go to sleep be-tween 10:00-11:00 PM and wake up between 5:00-6:00 AM. This comprises 7-9 hours of sleep. Teachers also go to church or other re-ligious meetings once a week and also, they pray, meditate, or study the Bible more than once a week. Also, most of the responses of teach-ers in the suicidal thoughts were either